Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Pegawai PT. Sinar Galesong Pratama - Ummu Humaira Ridwan; Chalid Imran Musa; Uhud Darmawan Natsir (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This research aims to determine whether there is a significant positive influence on Leadership Style and Work Motivation on Employee Performance. The research method used in this research is quantitative. The population in this study were employees at PT. SINAR GALESONG PRATAMA (Suzuki) as many as 40 people. Data collection techniques use observation, interviews and questionnaires. The data analysis techniques used are multiple linear regression test, partial test (t test), simultaneous test (f test), and coefficient of determination test (R2). Based on the research results, multiple linear regression results were obtained which showed the equation Y = 4.464 + 0.355X1 + 0.691X2 + e and based on the test results, the coefficient of determination of the influence of Leadership Style and Work Motivation on Employee Performance was r = 0.601. The coefficient of determination (r2) for this factor has a value of 0.361 or 36.1%, the remaining 63.9% is influenced by other variables not included in this research model. This is proven by statistical tests showing that the tcount = 1.478 and 1.886 are smaller than ttable = 2.026. The calculation results obtained show that the leadership style variable does not have a positive influence and the work motivation variable does not have a positive influence on employee performance and the hypothesis results are not accepted.